2006
DOI: 10.1534/genetics.106.059709
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Gametophytic baseless1 Is Required for Development of the Central Cell and Early Endosperm Patterning in Maize (Zea mays)

Abstract: In angiosperms, double fertilization of an egg cell and a central cell with two sperm cells results in the formation of a seed containing a diploid embryo and a triploid endosperm. The extent to which the embryo sac controls postfertilization events in the seed is unknown. The novel gametophytic maternal-effect maize mutation, baseless1 (bsl1) affects central cell development within the embryo sac, frequently by altering the position of the two polar nuclei. Despite this irregularity, fertilization is as effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
53
0
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 59 publications
(70 reference statements)
2
53
0
1
Order By: Relevance
“…Transfer cell fate specification apparently occurs during a narrow temporal window of syncytial development, as shown by the phenotype of the maize globby-1 mutant, which has an abnormal basal layer of transfer cells . Patterning events in the central cell of the maize embryo sac are also important for patterning of the transfer cell layer (Gutierrez-Marcos et al, 2006a). Three groups of maize genes are preferentially expressed in transfer cell layers, BETL, BAP, and EBE (Magnard et al, 2003).…”
Section: Transfer Cellsmentioning
confidence: 99%
“…Transfer cell fate specification apparently occurs during a narrow temporal window of syncytial development, as shown by the phenotype of the maize globby-1 mutant, which has an abnormal basal layer of transfer cells . Patterning events in the central cell of the maize embryo sac are also important for patterning of the transfer cell layer (Gutierrez-Marcos et al, 2006a). Three groups of maize genes are preferentially expressed in transfer cell layers, BETL, BAP, and EBE (Magnard et al, 2003).…”
Section: Transfer Cellsmentioning
confidence: 99%
“…The single-celled zygote soon acquires the potential to develop into an embryo undergoing a series of complex cellular and morphological processes that finally produce the sporophyte or plant (Rao, 1996). Further information in these topics can be found in Russell (1992); Rotman et al (2003); Gutiérrez-Marcos et al (2006); He et al (2007) and Capron et al (2008), among many others.…”
Section: Zygotic Embryogenesismentioning
confidence: 99%
“…Since some maternal effect mutants cause kernels to develop patches lacking aleurone (Gavazzi et al 1997) or BETL (Gutierrez-Marcos et al 2006), and some zygotic mutants ectopically express aleurone tissue (Costa et al 2003), we examined the expression of markers for these two tissues. For aleurone, we crossed stt1/1 females by males carrying Pro Vp1TGUS and stained for GUS activity in mutant and wild-type endosperms at 20 and 34 DAP (Figure 7) (Cao et al 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Studies of these mutants and others have revealed several causes for maternal effects. Possible mechanisms include: changes in functional gene dosage in the endosperm (e.g., floury3; Ma and Nelson 1975), abnormal embryo sac morphology (e.g., baseless1; Gutierrez- Marcos et al 2006), loss of embryo sac proteins normally stored cytoplasmically to act after fertilization (perdurance) (e.g., PROLIFERA; Springer et al 2000), or imprinting (e.g., Polycomb group and other genes in maize and Arabidopsis (recently reviewed in Huh et al 2008;Johnson and Bender 2009;Jullien and Berger 2009). Known maternal gametophyte effect mutants are involved in basic cellular process, such as DNA demethylation, DNA repair, and cell cycle regulation, as well as seed specific processes such as the suppression of autonomous endosperm development (Golden et al 2002;Holding and Springer 2002;Ngo et al 2007;Andreuzza et al 2009).…”
mentioning
confidence: 99%
See 1 more Smart Citation